Ergonomic considerations for designing truck drivers' seats: The case of Bangladesh. Issue 1 (25th January 2018) - Halder, Pobitra; Mahmud, Tamanna; Sarker, Eity; Karmaker, ChitraLekha; Kundu, Sazal; Patel, Savankumar; Setiawan, Adi; Shah, Kalpit
Abstract : Objectives: The purpose of this work was to investigate the fitness of the existing truck seats for Bangladeshi truck drivers and suggest a guideline for drivers' seats based on their anthropometry. Methodology: In this study, eight anthropometric measurements of 120 Bangladeshi truck drivers and seven seat dimensions of ninety trucks of three brands namely, TATA, ASHOK LEYLAND, and ISUZU were considered for investigating the considerable mismatch between seat dimensions and drivers' anthropometry. The data were analyzed using two‐sample t‐tests to identify the relationship between existing seat dimensions and drivers' anthropometry. Results: The results showed a mismatch in seat dimensions and anthropometric measurements for nearly all truck brands and the existing seat dimensions were found to be inappropriate for Bangladeshi drivers. For all the truck brands, the percentage mismatch of seat height, seat depth, seat width, backrest height, and steering wheel clearance varied between 71% and 98%, 23% and 79%, 33% and 84%, 28% and 65%, and 53% and 100% respectively. Subsequently, an attempt was made to provide ergonomically correct seat dimensions for Bangladeshi truck drivers. Further, generalized equations to design the appropriate seat dimensions were developed using the least square regression technique. The recommended seat height, depth and width, backrest height, and steering wheel clearance were found to be appropriate for 82%, 79%, 76%, 98%, and 100% of drivers respectively. Conclusion: The analysis and results of this study can be useful in developing guidelines for design and manufacture of truck driver seats in Bangladesh.